Exploring the effects of outdoor physical work in the heat, with or without sodium bicarbonate supplementation, on markers of acute kidney injury - Jason Siegler; Brooke Butterick; Raul Freire; Jonathan Specht; Fabiano Amorim (Physiological Reports)
Abstract Acute kidney injury (AKI) has been observed after prolonged physical activity in the heat. Although a range of strategies to reduce the incidence of AKI have been investigated, sodium bicarbonate (SB) supplementation may mitigate metabolic stress during physical exertion and potentially alleviate renal workload by lowering glomerular filtration demand, reducing bicarbonate reabsorption, and preserving kidney microcirculation. Therefore, the primary objective of this study was to investigate the effect of SB ingestion on markers of AKI. Fourteen healthy men and women (n = 6) completed two (SB & placebo) experimental 2‐hr outdoor work sessions in the heat (~35°C; ~20% humidity) designed to simulate construction tasks. Changes in acid–base balance, markers of kidney injury (NGAL, TIMP2, IGFBP‐7), thermotolerance, and work achieved throughout the experimental trials were analyzed using a linear mixed model with two‐way repeated measures. Despite inducing a significant level of alkalosis in the SB trial (7.40 ± 0.03 vs. 7.45 ± 0.03; p < 0.001), no changes were observed in urinary NGAL, TIMP2, or IGFBP‐7 concentrations (p > 0.27). Core temperature and heart rate were elevated throughout the work session in the SB condition (mean increase of 0.2 ± 0.1°C and 9 ± 3 bpm; p < 0.025), but the rating of perceived effort was lower when compared to placebo (0.3 ± 0.1 au; p = 0.003). Although the environmental and work stress in the present study did not influence markers of acute AKI, participants were less sensitive to increases in thermoregulatory and cardiovascular strain during a state of metabolic alkalosis.